MODERN METHODS OF TEACHING FOREIGN LANGUAGES AND TECHNIQUES OF TEACHING IN A SHORT TIME (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER'S THEORY, 2023)
This article is about different methods in teaching foreign languages. For the last 20 years connections have been becoming inevitable among nations, states, organizations and countries which create a huge need for knowing another language or more multilingualism. People need to use international languages in areas such as trade, tourism, international relations between governments, technology, science and media. Here we show how to use methods of teaching from different countries. Some countries such as China and Japan prefer to teach at least one foreign language at primary and secondary school level. Teachers of all countries try to use different methods in teaching language they proper.